An Ultrasound-Guided Thoracolumbar Erector Spinae Plane Block: An Experimental Preliminary Study in Horses - Francisco Medina-Bautista; Irene Nocera; Antonia Sánchez de Medina; Chiara Di Franco; Angela Briganti; Juan Morgaz; María del Mar Granados (Animals)
The objective of this study was to evaluate the feasibility and efficacy of the ultrasound-guided thoracolumbar erector spinae plane (TL-ESP) block in standing horses. A total of 24 injections (n = 12) were performed at the L1 level using either 0.1 mL/kg of saline solution (SS group) or 2% lidocaine (LID group). The block feasibility was assessed based on needle visualization and injection time, while efficacy was evaluated through craniocaudal and dorsoventral (DV) spread using the pinprick technique over 270 min. Desensitization was observed at least once in 100% of horses in the LID group and in 75% in the SS group (p = 0.001). However, in the SS group, desensitization was primarily limited to the Th18 metamer at the 2 cm DV position, with a shorter duration compared to the LID group. The block onset occurred at 22.5 (11.25–60) min in the LID group and at 5 (5–30) min in the SS group (p = 0.069). The number of affected metamers was significantly higher in the LID group (2 [1–3]) compared to the SS group (1 [1–2.25], p = 0.014). At the 2 cm DV point, the end of the block effect occurred at 135 (120–210) min in the LID group and at 60 (3.75–60) min in the SS group (p = 0.001). Needle visualization was excellent in 95.8% of cases, and the mean injection time was 2.5 (2–3) min. These findings confirm that the TL-ESP block is a feasible technique in standing horses. However, its effect is predominantly localized to dorsal dermatomes with a limited ventral spread. Future studies evaluating larger volumes and multiple injection sites are warranted to enhance its clinical applicability.